Enhanced Tribological Properties of Ethylene Glycol-Based Lubricants by Nitrogen–Phosphorus Co-Doped Carbon Dots - Haiyang Wang; Zhongyi He; Kai Qiu; Liping Xiong; Lili Li; Jian Liu (Lubricants)
In this study, we successfully synthesized two types of nitrogen–phosphorus co-doped carbon dots (CDs), namely 6NP-CDs and eNP-CDs, and incorporated them as additives into ethylene glycol-based lubricants. We systematically evaluated the effects of these CD additives on the tribological properties of the lubricants through four-ball friction experiments. The experimental results demonstrate that lubricants enhanced with the CDs exhibit significantly improved tribological properties compared to the base lubricant, particularly in terms of anti-wear performance. Notably, 6NP-CDs exhibited superior wear resistance and friction reduction at concentrations of 0.1 wt.% and 0.2 wt.%. Furthermore, increasing the concentration of eNP-CDs further reduced the friction coefficient of the base lubricant, and at its optimal concentration, it outperformed 6NP-CDs in terms of wear resistance and friction reduction. Molecular structure analysis indicates that the concentration of nitrogen and phosphorus atoms, as well as the chain length of functional groups, significantly influence friction characteristics. Specifically, a greater content of heteroatoms and longer chain lengths correlate with improved friction performance. The results suggest that incorporating 6NP-CDs and eNP-CDs into ethylene glycol-based lubricants can lead to significant enhancements in tribological performance under heavy loads.